Herramienta computacional que permite simular la presión interna del riñón provocada por litiasis renal (2022)
The proposal of this research focuses on the analysis of the internal pressure of the kidney, as well as its changes generated from the obstruction of a kidney stone, which can vary in size and position within the kidney and its urethra, which allows show the effect of the pressure generated by said obstruction inside it. The objective of this research is to identify the pressure changes generated from the renal obstruction caused by lithiasis; For this, it uses a series of 2D and 3D simulations that allow us to visualize the small changes generated by the Obstruction, as well as being able to generate a report with the results of the configuration incorporated in the computational tool. The software allows the placement of stones of different sizes and in various positions along the physiology of the kidney and/or its ureter. The application is portable and can be run on any computer with a Windows operating system. The results obtained allowed us to identify the different pressure changes exerted by the renal lithiasis. In the same way, it is possible to observe the changes in fluid velocity with and without kidney stones, likewise, an interface was developed that facilitates the modification of some parameters such as the position and size of the lithiasis and to observe through images and a subsequent report. of the results obtained from the simulation. The validation of the designed software was carried out with professionals in the health area, 3 specifically with general practitioners and specialists, the results were satisfactory and there are great ideas for the future tool.